From Classroom To Public Space: How Communication Education Shapes Critical Citizenship - Farah Diba; Rika Handayani; Ludfi; Dedi Andrianto; Muhamad Towil Akhirudin (Qoumun: Jurnal Pengabdian Masyarakat, 2026)
Purpose of the study: This study aimed to map how classroom communication education practices transform into citizens' critical participation capacities in the public sphere, addressing fundamental questions raised by the digital public sphere's transformation, marked by polarization, misinformation, and discursive fragmentation. Methodology: A Systematic Literature Review (SLR) using the PRISMA approach was applied, based on 47 Scopus- and Sinta-indexed articles published between 2015 and 2025. Main Findings: The findings reveal four main dimensions connecting communication education with critical citizenship: critical media literacy, dialogic pedagogy, deliberative digital participation, and resistance to dominant discourses. The study concludes that communication education should be reconceptualized as a transformative social praxis, integrating Habermasian public sphere theory, Freirean critical pedagogy, and digital citizenship approaches to address contemporary challenges to deliberative democracy. Novelty/Originality of this study: The novelty lies in the systematic integration of Habermasian public sphere theory, Freirean critical pedagogy, and digital citizenship approaches into a single transformative social praxis framework for communication education specifically mapping how classroom practices translate into critical participation capacities in the digital public sphere an integrative model not previously documented in the context of addressing polarization, misinformation, and discursive fragmentation in contemporary deliberative democracy.